Collaborative quality improvement reduced ventilator-associated pneumonia in a limited resource country - Unahalekhaka, Akeau (International Journal of Infection Control, 2008)
Ventilator-associated pneumonia (VAP) is a hospital-acquired infection with the highest case fatality rate in Thailand. A collaborative approach among multidisciplinary professionals across 18 hospitals in three regions of Thailand had led to a considerable reduction in VAP among mechanically ventilated patients admitted in intensive care units. By applying the collaborative quality improvement concept, participating hospitals experienced a gradual decrease in the trend of the VAP rate per 1000 ventilator-days. Surveillance systems for VAP have improved and the approach had led to advances in the care of mechanically ventilated patients, resulting in the reduction of VAP incidence.